TANTANGAN PROGRAM KAMPUS MENGAJAR ANGKATAN 7 DI SD LINGGAWASTU BANDUNG - Hayati, Nur; Ritonga, Duma Soswati (Sekolah Tinggi Ilmu Ekonomi AMA, 2025)
The Teaching Campus Program 7 is an initiative launched by the Ministry of Education, Culture, Research, and Technology of Indonesia designed to enhance the standard of education in primary schools, especially in underserved regions. During the execution of Teaching Campus 7 at SD Linggawastu in Bandung, students take on active roles as educators and guides in various teaching and learning experiences, while also helping to improve students' skills in literacy, numeracy, and character development. This initiative incorporates a range of creative and innovative instructional strategies tailored to match the diverse needs and attributes of learners at Linggawastu Elementary School. Additionally, students are involved in programs that focus on mentoring teachers, creating educational materials, and conducting extracurricular activities aimed at fostering students’ social and emotional development. The outcomes of this initiative indicate a rise in students' motivation to learn, improvements in their literacy and mathematics skills, and enhanced cooperation among students, educators, and school administrators. The Teaching Campus Program 7 at Linggawastu Elementary School is anticipated to act as a blueprint for collaborations between institutions of higher learning and primary schools, contributing to the overall enhancement of education in Indonesia.